INTERACTIVE BLOCK GAMES TO IMPROVE VISUAL SPATIAL INTELLIGENCE IN EARLY CHILDHOOD - wiwik sulistyawati (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
The development of technology and modern lifestyle has changed children's play patterns, where more time is spent with digital devices than manipulative activities that support visual-spatial development, interactive block play is a popular activity for preschool children and has been considered by researchers as a versatile activity to help children develop technological thinking, critical thinking, problem solving, creativity, and abstract thinking, Data collection was carried out through systematic observation, documentation, and performance tests to measure the development of children's visual-spatial intelligence. The collected data were analyzed using the independent sample t-test statistical test, and the paired sample t-test to analyze the increase in scores from pretest to posttest. The validity and reliability of the instrument trial instrument with a Cronbach's alpha reliability value> 0.7. based on the Sig. (2-tailed) value in the experimental class of 0.010 <0.05. So there is a difference before the intervention or pretest and after the intervention or posttest. Therefore, there is an influence of interactive block play to improve visual spatial intelligence in early childhood. Children who regularly play with interactive blocks show improvements in several cognitive aspects. They have better abilities in recognizing patterns, understanding spatial relationships, and solving problems involving spatial orientation